Human resource management in islamic perspective (case study At Ibu Pejabat Polis Kontinjen Kelantan) / Norme Yajid - Yajid2014209426, Norme (2016)
The purpose of this conceptual paper is to enlighten academicians and organizations with effective ways of understanding and implementing HRM by using Islamic principles The purpose of this study is to explore and examines the theoretical frameworks of Islamic human resource management practices. Additionally, to investigate the extent to which Islamic HRM practices inspire and revival employees trust in organization. This study comprised sample of 217 employees from Ibu Pejabat Polis Kontinjen Kelantan. A descriptive study research design was used to examine the relationship between human resource management activities with Islamic human resource practice. Data were gathered based on personal administered questionnaire. As the conclusion, the finding of this research shows that recruitment, selection and performance appraisal are significantly being practice in Ibu Pejabat Polis Kontinjen Kelantan. But training and development and compensation are found have insignificant relationship